Health Disturbances of Negative Nutritional Shocks - Zare Markovic; Vedad Hodzic; Hossein Shahri (Budapest International Research and Critics University, 2021)
The Fetal Origin Hypothesis show that the prenatal development period is a critical period for birth outcomes. Applying a panel data fixed effect model and using the universe of birth records in the US, I find that exposure to the holy month Ramadan, during which Muslim mothers fast for the whole day, during prenatal development has negative birth outcomes. Exposure to a full month of fasting is associated with 96 grams lower birth-weight. These results are robust across specifications and do not appear to be driven by mothers’ selective fertility.